AIDS, identity, and community : the HIV epidemic and lesbians and gay men - Greene, Beverly; Herek, Gregory M. (Psychological perspectives on lesbian and gay issues, 1995)
Hit hard by the AIDS epidemic in the United States and in much of Europe, the gay and lesbian community has been forced to examine existing notions of what it means to belong to a community based on sexual orientation. The editors of this second volume in the annual series on Psychological Perspectives on Lesbian and Gay Issues have collected a perceptive array of chapters that explore sexual behavior, personal identity, and community memberships of gay men and lesbian women. With the exception of a few, the chapters reflect study findings from AIDS-related research and include discussions of AIDS in large urban centers and in less populated settings outside of major AIDS epicenters. Focusing on underconsidered AIDS populations, the contributors explore specific topics concerning the AIDS epidemic among gay and bisexual men of color, lesbian women, and gay and lesbian youth.